The Influence of RME on Mathematical Problem Solving of Students at SDN 49 Parepare - Yonathan S Pasinggi (Darul Yasin Al Sys, 2026)
Although mathematical problem-solving ability has become a central concern in elementary mathematics education, empirical discussion of Realistic Mathematics Education (RME) in the specific context of SDN 49 Kota Parepare remains limited. This study aims to analyze the effect of RME on fourth-grade students’ mathematical problem-solving ability. A quantitative approach with a quasi-experimental nonequivalent control group design was employed. The manuscript was prepared using a simulated dataset involving 48 fourth-grade students, comprising 24 students in the experimental class and 24 students in the control class, selected through cluster sampling. Data were collected using a mathematical problem-solving essay test based on four indicators: understanding the problem, planning a solution, implementing the plan, and checking the answer. Data were analyzed using descriptive statistics, N-gain, the Shapiro–Wilk normality test, Levene’s homogeneity test, and an independent-samples t-test. The simulated findings show that the experimental class increased from a mean pretest score of 48.17 to a mean posttest score of 81.83, whereas the control class increased from 49.79 to 71.54. The experimental class obtained an N-gain score of 0.66, which was higher than the control class score of 0.44. Hypothesis testing indicated a significant difference in N-gain scores, t(46) = 5.19, p < .001, with a large effect size. These findings illustrate that RME can support contextual, model-based, interactive, and reflective mathematics learning, particularly in strengthening students’ mathematical problem-solving processes. The study contributes to elementary mathematics education by demonstrating the potential of RME as an instructional approach for improving problem-solving ability; however, before scholarly submission, the simulated data must be replaced with actual field data from SDN 49 Kota Parepare.